Knowledge and Adoption of Chickpea Cultivation Technologies under Cluster Front Line Demonstrations among Farmers of Bikaner, Rajasthan - , Om Prakash Choudhary, Rajesh Kumar Verma, Aravindh Kumar S, Ravindra Singh Choudhary (Archives of Current Research International, 2025)
The impact of the Cluster Front Line Demonstration (CFLD) program—implemented by KVK Bikaner-I under the National Food Security Mission in the arid region of Bikaner, Rajasthan was assessed to determine its influence on farmers’ uptake of improved chickpea cultivation practices. A total of 200 growers (100 CFLD participants and 100 non-participants) were drawn by proportionate random sampling from Bikaner and Kolayat tehsils. Data were collected through structured interviews, standardized knowledge tests, and adoption checklists to capture two dependent measures (knowledge level and extent of adoption) alongside eleven independent variables: age, caste, education, social participation, occupation, landholding, irrigation source, mass-media exposure, extension-agency contact, information-seeking behaviour, and information-sharing behaviour. Descriptive analysis showed that beneficiaries held larger average land parcels (5.45 ± 1.38 ha) and scored higher on—mass-media exposure (19.54 ± 6.07) and extension contact (18.66 ± 6.72)—than non-beneficiaries. Mean knowledge and adoption scores were significantly greater among CFLD participants. Pearson’s correlation revealed strong positive associations between both knowledge and adoption and four communication factors (mass-media exposure, extension contact, and information-seeking and sharing behaviours; r > 0.52, p < .01), and moderate positive links with education (r ≈ 0.47–0.66, p < .01). Age exhibited a small negative correlation (r ≈ –0.24, p < .05). Caste and social participation showed weaker yet significant relationships with knowledge among beneficiaries (r ≈ 0.24–0.29, p < .05). Overall, participation in CFLD was associated with higher knowledge and technology adoption, underscoring the program’s effectiveness in technology diffusion. It was concluded that proactive communication and targeted training drove these gains. Future extensions should focus on including non-participant cohorts particularly the older and less-educated farmers by intensifying digital and mass-media outreach, strengthening peer-learning networks, and institutionalizing follow-up visits to sustain technology uptake and enhance chickpea productivity in arid agro-ecosystems.